2022
DOI: 10.7150/thno.68864
|View full text |Cite
|
Sign up to set email alerts
|

Macitentan improves antitumor immune responses by inhibiting the secretion of tumor-derived extracellular vesicle PD-L1

Abstract: Extracellular vesicles (EVs) carrying tumor cell-derived programmed death-ligand 1 (PD-L1) interact with programmed death 1 (PD-1)-producing T cells, thus significantly lowering a patient's response to immune checkpoint blockade drugs. No drug that reinvigorates CD8+ T cells by suppressing EV PD-L1 has been approved for clinical usage. Here we have identified macitentan (MAC), an FDA-approved oral drug, as a robust booster of antitumor responses in CD8+ T cells by suppressing tumor cell-derived EV PD-L1. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 75 publications
0
39
0
Order By: Relevance
“…Moreover, sulfisoxazole and macitentan are FDA-approved antagonists of endothelin receptor A (ETA) which regulates the expression of a series of genes associated with exosome biogenesis, such as Rab27a and Vps4B. Both of these drugs could reduce the exosomal secretion of PD-L1 and improve the response to anti-PD-1/PD-L1 therapy in cancer, such as breast, colon, and lung cancer [ 211 , 212 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, sulfisoxazole and macitentan are FDA-approved antagonists of endothelin receptor A (ETA) which regulates the expression of a series of genes associated with exosome biogenesis, such as Rab27a and Vps4B. Both of these drugs could reduce the exosomal secretion of PD-L1 and improve the response to anti-PD-1/PD-L1 therapy in cancer, such as breast, colon, and lung cancer [ 211 , 212 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it is reported that inhibiting sEV PD-L1 secretion could improve the efficacy of anti-PD-L1 and anti-cancer immunity because tumor-derived sEV and sEV PD-L1 contribute to tumor growth and immune evasion by inhibiting T cell activity, such as NF-κB, IL-2, and IFN-γ activation [ 38 , 39 ]. Furthermore, we previously confirmed that suppression of sEV PD-L1 secretion through the inhibition of tumor-derived sEV secretion by the ETA antagonists sulfisoxazole and macitentan caused the activation of immune cells, thereby exhibiting anti-cancer effects [ 16 , 17 , 18 ]. Next, it is known that inhibition of PD-L1 expressed by cancer cells can activate the immune system in the body [ 39 ].…”
Section: Discussionmentioning
confidence: 88%
“…Moreover, it was reported that PD-L1 secreted from the tumor sEV binds to PD-1 on immune cells and induces immune evasion, resulting in a low response to ICBT [ 13 , 14 , 15 ]. Recently, we reported a new paradigm for cancer treatment by identifying mechanisms by which endothelin A (ETA) antagonists improve anti-cancer immunity in the body by inhibiting the secretion of tumor-derived sEV and sEV PD-L1 [ 16 , 17 , 18 ]. Therefore, the inhibition of sEV secretion and PD-L1 from tumor cells can enhance the response to ICBT.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, exosomes are associated with immune escape that can be driven by tumor associated macrophages and neutrophils ( Kim and Bae, 2016 ). Interaction between exosome-carried programmed death ligand 1 (PD-L1) and T-cells that produce programmed death 1 (PD-1), significantly reduce the response to immune checkpoint blocking drugs ( Lee et al, 2022 ). Consequently, exosomes have emerged as one of the key mechanisms regulating the immunotherapy of malignant tumors and it is crucial to investigate exosome-related prognostic signature in COAD patients.…”
Section: Introductionmentioning
confidence: 99%